Progress in Water Footprint Assessment - Van Oel, Pieter (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Water Footprint Assessment is a young research field that considers how freshwater use, scarcity, and pollution relate to consumption, production, and trade patterns. This book presents a wide range of studies within this new field. It is argued that collective and coordinated action - at different scale levels and along all stages of commodity supply chains - is necessary to bring about more sustainable, efficient, and equitable water use. The presented studies range from farm to catchment and country level, and show how different actors along the supply chain of final commodities can contribute to more sustainable water use in the chain.